CREATION OF THE JAPANESE ETHNIC IDENTITY ON THE BASIS OF MODERN CHILD REARING CONCEPT (Journal of Oriental Studies, 2019)
The article illustrates an example of modern Japanese society’s uniqueness model in the framework of program “Spiritual Renewal” published by the President of the Republic of Kazakhstan. The basis of the Japanese society’s unity is the formation of ethnic identity that is focused on the national charac teristics of family institution. Particularly, the upbringing of a Japanese citizen starts with child rearing, including the concept of “amae”, which is the development of personality through the relationship be tween the child and mother.Key words: Spiritual renewal, identity, japanese family, concept of «amae», Japan.